Issues of E-learning in developing countries: a Nigerian perspective - Balogun, Naeem Atand; Ahlan, Abdul Rahman (2014)
This study aims to highlight the existing issues of e-learning in the developing country such as Nigeria. As e-learning becomes important in the delivery of education with less consideration for distance, time and cost, however, it is still a dream in some part of the world as some issues are presently unavoidable and rendered this important aspect of knowledge gain a less resourceful in Nigeria as a developing country. Issues such as computer ownership, internet access, epileptic electricity and internet experience are highlighted to have hindered e-learning. This study considered only Nigeria as a developing country; hence having the highest number of internet users in Africa.